Development of a superhydrophobic polyurethane-based coating from a two-step plasma-fluoroalkyl silane treatment. (July 2016) - West, J.O.F.; Critchlow, G.W.; Lake, D.R.; Banks, R.
Abstract: A method of achieving a superhydrophobic surface based upon a highly filled polyurethane (PU) paint coating has been demonstrated through the use of a combined oxygen/argon plasma pretreatment and a fluoroalkyl silane (FAS) final treatment. The combined plasma-FAS treated PU surface has been investigated and characterised using: field emission gun secondary electron microscope (FEG-SEM); X-ray photoelectron spectroscopy (XPS); energy-dispersive X-ray spectroscopy (EDX); water contact angle analysis (WCA); atomic force microscopy (AFM), and; Fourier transform infrared spectroscopy (FTIR). It was found that the oxygen/argon plasma treatment increased both the surface roughness (Ra ) and surface free energy (SFE) of the PU paint coating from approximately 60–320 nm, and, from ~52 to ~80 mN/m respectively. It was also found that the plasma process created a multiscale roughened texture through the process of differential ablation between the PU polymer and the barium sulphate solid content, which is present in the paint as an extender, and other additives. In addition, the process also imparted favourable polar groups into the PU surface from the ionised and radical oxygen species in the plasma. When the FAS coating was subsequently applied to the PU without prior plasma treatment, there was a significant increases in water contact angles. This parameter increased from approximately 60° on untreated PU to around 130° with FAS applied. In this case, the SFE decreased to ~7.5 mN/m and showed 42.0 at% fluorine present as indicated by XPS. However, subsequently applying the FAS polymer after plasma pretreatment takes advantage of the known synergistic relationship that exists between surface roughness and low surface free energy coatings. The two processes combined to create superhydrophobicity with a surface that exhibited water contact angles up to 153.1°. With this optimised process, the apparent SFE was 0.84 mN/m with a more highly fluorinated surface present. In this case 47.2 at% surface fluorine was observed by XPS. In addition to changes in SFE, plasma treatment was also observed to alter levels of surface gloss and colour. After exposure to 600 s of plasma gloss levels are shown to reduce from values of from ~50 to ~21 (GU), with small but significant corresponding increases in the lightness and yellowness of the surface.